Association between dietary mineral intakes and urine flow rate: data from the 2009–2018 National Health and Nutrition Examination Survey - Li, Ming; Zhang, Jiqian; Ding, Jiasen; Gao, Zhan (Frontiers in Nutrition, 2024)
Background: Minerals play an important role in human health, but their effect on urinary function remains controversial. The aim of this study was to assess the association between dietary intake of minerals (Ca, P, Mg, Fe, Zn, Cu, Na, K, Se) and urine flow rate (UFR).We conducted a cross-sectional study using the National Health and Nutrition Examination Survey (NHANES, 2009(NHANES, -2018) ) database. Multivariate regression and smooth curve fitting were used to investigate the association between dietary mineral intakes and UFR. Subgroup analyses and interaction tests were used to investigate whether this association was stable in the population.Results: Our study involving 10,229 representative adult NHANES participants showed an association between Mg intake and UFR in a linear regression model for continuous variables. And in the model analysis of tertile categorical variables, we observed a positive association between six mineral intakes (Ca, Mg, Zn, Cu, Na, and K) and UFR. Smoothed curve fitting and threshold effect analysis further support the nonlinear relationship between mineral intakes and UFR. Subgroup analyses and interaction tests ensured the reliability and robustness of the findings.This study examined the effects of nine dietary minerals on UFR and found that intake of Ca, Mg, Zn, Cu, Na, and K were positively correlated with UFR, suggesting that these minerals may have a positive effect on improving urinary function. In particular, Mg showed a more significant positive correlation with UFR in women, while Na showed a stronger positive correlation in diabetics. However, P, Fe and Se did not show significant correlations. In summary, although these findings provide a preliminary understanding of the relationship between dietary minerals and urinary function, further prospective studies are still necessary to validate these relationships and explore the physiologic mechanisms underlying them.